Model Pembelajaran Kooperatif Tipe Make a Match Untuk Meningkatkan Hasil Belajar - Cahyo Purnomo (Academia Publication, 2021)
This classroom action research aims to improve the learning outcomes of class VIII H students of SMP Negeri 1 Turi with the Make a match type of Cooperative Learning model on straight-line equations. The Make a match type of Cooperative Learning Model is one of the Cooperative Learning models where students work together to find their respective partners. This research consists of two cycles. Each cycle consists of four stages, namely: planning, implementation, observation, and reflection. Collecting data using field notes, observations, tests and interviews. Data collection tools are observation sheets, interview guidelines, and questions. Data analysis in this classroom action research uses descriptive analysis techniques.The results obtained in this study: cycle 1 was carried out for 2 meetings with the results of the percentage of students whose scores were above the KKM as much as 53.33%. Cycle 2 was conducted for 2 meetings with the result that the percentage of students whose scores were above the KKM was 76.67%. Based on the results of the study, it was found that the Make A Match Cooperative Learning Model could improve the learning outcomes of 8th grade students of SMP Negeri 1 Turi.